IMPLEMENTATION OF TRANSDISCIPLINARY APPROACH AS A MEANS OF FORMATION OF NATURAL AND MATHEMATICAL COMPETENCE OF FUTURE SEAMEN - Plotnikova, Olena; Korobova, Iryna (Physical and Mathematical Education, 2021)
Modern Ukrainian education is in the process of reform. Oversaturation of the labor market with humanitarian specialists does not contribute to the active development of the economic sector of our country. That is why the Ministry of Education and Science of Ukraine shifts the emphasis from the disciplines of the humanities to the disciplines of the natural and mathematical cycle. At the same time, in the process of professional activity, specialists in all fields (including maritime) face problems, the solution of which requires interdisciplinary knowledge, ie, they need to show their competence. The basis for the training of such specialists is the introduction of a transdisciplinary approach into the educational process, which today is a necessary condition for the development of education in general. In addition, the implementation of a transdisciplinary approach provides an opportunity to intensify the cognitive activity of applicants, promotes the formation of their professional qualities, in particular, natural and mathematical competence. Problem formulation. The purpose of the article is to analyze the features of the transdisciplinary approach and identify opportunities for its implementation in the process of forming the natural and mathematical competence of future sailors. Materials and methods. Theoretical and empirical research methods are used in the work, such as analysis of literature sources, synthesis, observation of the educational process, systematization and generalization of research results. Results. The paper presents an example of a competency task constructed within a transdisciplinary approach. The experience of using competence tasks in the training of future seafarers has proved their effectiveness, as they provide ample opportunities to involve future professionals in solving practical problems close to the professional activities of future seafarers, which in turn contributes to the formation of their natural and mathematical competence. Conclusions. It is proved that the transdisciplinary approach is relevant today and provides ample opportunities for teachers to achieve the goals of the educational process. In addition to the fact that a transdisciplinary approach is a necessary condition for the development of modern education, it is also a guarantee of successful formation of natural and mathematical competence of future sailors, which requires the applicant to demonstrate integrated knowledge of mathematics, physics and computer science in solving professional problems. One of the ways to implement a transdisciplinary approach in the educational process is to involve applicants in solving competency problems.